Innuendo, Ambiguity and Uncertainty: Reading Keys and Aesthetic Effects of the Ambiguous Pact - Escobar Vera, Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Based on current debates on the definitions of autofiction and ambiguous pact, this article explores their boundaries and exclusions, proposing conceptual precisions aimed at focusing on some problems of in creasing importance, that appear to exceed canonic definitions. Emphasis will be placed on textual and extratextual innuendos present in works based on the ambiguous pact, such as figurations of the author, the role of the reader and the effects of ambiguity, the weakening of truth and uncertainty.